PERSPEKTIF VIKTIMOLOGI TERHADAP KORBAN CHILD MALTREATMENT (Studi Kasus Pada Dua Anak Berinisial AP dan PI di Kota Pekanbaru) - Nurhalimah, Siti; Rinaldi, Kasmanto (SISI LAIN REALITA, 2022)
This study examines and discusses the problem of children who are victims of violence within the family. This is motivated by the endless number of acts of violence against children. Children should get protection and love by their families, but now children are even victims of violence by their own families and even their own parents which is called child maltreatment. But what is unfortunate is that this is considered normal by the community. Violence that usually occurs by children includes physical violence, psychological violence, sexsual violence, and social violence. In this study, we want to discuss what forms of child maltreatment are and what causes child maltratment, where we know that acts of violence will be dangerous in the development and life of the child. The research method used in this research is qualitative research which aims to describe the actual situation of what is happening at the research site through collecting, identifying, and analyzing data so as to obtain answers to the formulated problems. So this study concludes that the cause of child maltreatment victims is due to parental disputes and lack of understanding in educating children and lack of concern for the surrounding community. This is expected to be a lesson so that no more children become victims of domestic violence committed by their own parents